2020
DOI: 10.1111/ejh.13390
|View full text |Cite
|
Sign up to set email alerts
|

Clonal selection in therapy‐related myelodysplastic syndromes and acute myeloid leukemia under azacitidine treatment

Abstract: Introduction Therapy‐related myelodysplastic syndrome and acute myeloid leukemia (t‐MDS/AML) are defined as complications of previous cytotoxic therapy. Azacitidine (AZA), a hypomethylating agent, has showed activity in t‐MDS/AML. Objectives We evaluated the clonal dynamics of AZA‐treated t‐MDS/AML. Methods We collected bone marrow samples, at diagnosis and during treatment, from AZA‐treated t‐MDS/AML patients. NGS on 19 myeloid genes was performed, and candidate mutations with a variant allele frequency >5% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
(147 reference statements)
0
6
0
1
Order By: Relevance
“…Of note, we witnessed significantly lower relapse rates and NRM for transplant from female to male donor which probably might be related to enhanced graft vs leukemia effects without GVHD (non-tolerized donor T cells) against SMCY, which might have translated into survival/PFS benefit [27,28]. We found lower relapse rates among untreated patients as compared to patients who received treatment (irrespective of response and disease status-blast count), and this might be due to inability of treatment such as azacytidine to eliminate founder precursor clones, and emergence/selection of resistant clones while on treatment [29][30][31][32].…”
Section: Discussionmentioning
confidence: 73%
“…Of note, we witnessed significantly lower relapse rates and NRM for transplant from female to male donor which probably might be related to enhanced graft vs leukemia effects without GVHD (non-tolerized donor T cells) against SMCY, which might have translated into survival/PFS benefit [27,28]. We found lower relapse rates among untreated patients as compared to patients who received treatment (irrespective of response and disease status-blast count), and this might be due to inability of treatment such as azacytidine to eliminate founder precursor clones, and emergence/selection of resistant clones while on treatment [29][30][31][32].…”
Section: Discussionmentioning
confidence: 73%
“…Patients with TP53 mutations could benefit from AZA, which have been shown to confer better overall response rate to azacitidine than those with negative TP53 mutation in patients with higher-risk MDS (46% vs. 14%) [40,41]. Furthermore, decreased TP53-mutated clone was observed in patients with MDS/AML harboring TP53 mutation under AZA treatment [42]. VEN is a highly selective, potent BCL2 inhibitor, which induced apoptosis in malignant cells through BCL-2-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous SEER studies, we observed continued increase in tAML risk as stem cell transplantation and lenalidomide continue to remain a cornerstone of myeloma therapy 5 , 36 . A selective advantage of the RAS pathway gene mutations as well as TP53 clones 28 , 37 , 38 may have contributed to an increased risk for tAML after MM. It was interesting to note declining tMDS risk after MM.…”
Section: Discussionmentioning
confidence: 99%